Front Cover: Why Cyclopropanation is not Involved in Photoinduced α‐Alkylation of Ketones with Diazo Compounds (Eur. J. Org. Chem. 47/2018). Issue 47 (4th October 2018) - Rybicka‐Jasińska, Katarzyna; Orłowska, Katarzyna; Karczewski, Maksymilian; Zawada, Katarzyna; Gryko, Dorota
Abstract : The Front Cover shows porphyrin, a compound vital to our life that acts as a photoredox catalyst for the direct alkylation of carbonyl compounds with diazo esters. Based on experimental and theoretical studies, a plausible mechanism involving the generation of an enamine radical cation that subsequently reacts with protonated diazo compounds thus excluding the controversial cyclopropanation‐ring opening pathway is proposed. More information can be found in the Full Paper by K. Zawada, D. Gryko et al.